New Reflections on the Occupation of Jizzakh by the Mongols - M.Kh. Pardaev; G.I. Mo’minova (Indonesian Journal of Innovation Studies, 2019)
This article deals with the geographical location of the city of Djizzakh (Jizzak) during the Mongol invasion of Maverannahr. And also, due to the lack of written sources of information about the conquest of the city of Djizzakh by the Mongol hordes, the authors set forth their points of view on this important and interesting issue.